Contexto socioeducacional dos surdos de Soure - NEVES, Elis Regina da Silva (2019)
This article presents the socio educational context of deaf people from Soure. The main goal of this work was report information concerning the deaf people whom live in that city. This study also shom the importance of deaf people acquire their natural language in order to develop their skills. The results have showed the true truth about deaf people living Soure, trougth this research it was possible understanding the social and educational inequalities. We wish trough this researches about deaf people living in Soure.